Etika Komunikasi Netizen di Media Sosial (Analisis Komentar terkait Konten Keagamaan di Media X) - Hamidah, Ma'unatul; Yulia Silvi Yasmin; Nurul Hikma; Fitri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The development of information on social media is very rapid, one of the content that is of concern to netizens is religious content on social media X on the @Munir_Timur account uploading Pastor Gilbert's lecture that offends Muslim worship. The content went viral and became a public conversation. This study aims to explore how communication ethics are applied by netizens in the context of digital da'wah, using a qualitative approach and content analysis. Data were taken from comments on the account uploads, focusing on indicators of courtesy, effectiveness, efficiency, and mutual respect. The results show that (1) most netizens do not pay attention to good manners in their comments, using blasphemy, innuendo, and cursing, especially against content that is considered offensive to certain religions; (2) although they tend to be negative, some comments still meet the effective and efficient aspects of conveying messages; (3) there are netizens who prioritize mutual respect and open-mindedness, which reflects the potential of digital da'wah in encouraging more constructive dialogue.This research highlights the importance of media literacy and strengthening communication ethics in the context of digital da'wah, in order to create a more inclusive and dignified religious discussion space on social media.